БУЛГАКОВСКИЕ РЕМИНИСЦЕНЦИИ В РОМАНЕ ЧАПАЕВ И ПУСТОТА ВИКТОРА ПЕЛЕВИНА - Chudzińska-Parkosadze, Anna (Acta Neophilologica, 2018)
This article is devoted to the issue of reflecting ideas, motifs, themes, types of protagonists and conflicts of the novel The Master and Margarita by Mikhail Bulgakov in Pelevin’s novel Chapayev and Void. The central figure in Pelevin’s novel – Peter Emptiness (other versions of his name: Pyotr Pustota, Pyotr Voyd), reminds the reader of a hero from Mikhail Bulgakov’s novel – Ivan Homeless. The life situations of the respective heroes are analogous. The model of master and pupil is also an allusion to the relationship between Ivan and the Master. Pelevin’s reminiscence code also concerns the female hero Anna, who reflects Margarita as the ideal of beauty. Moreover, Pelevin seems to continue Bulgakov’s deliberations upon the evolution of Russian history, the constant and still valid conflict between the hero and Russian society. Additionally Pelevin uses the theme of spiritual initiation as the only way of escaping from the misery of Moscow’s reality